2006
DOI: 10.1111/j.1365-2036.2006.02970.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: antioxidant supplements for primary and secondary prevention of colorectal adenoma

Abstract: SUMMARY BackgroundColorectal cancer may be prevented by reducing the development of adenomatous polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 62 publications
8
56
0
5
Order By: Relevance
“…Some meta-analysis of randomized controlled trials also showed no evidence of a protective effect of supplement use on mortality or morbidity [3,5,6,8,9]. No evidences of a protective effect were found in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analysis of randomized controlled trials also showed no evidence of a protective effect of supplement use on mortality or morbidity [3,5,6,8,9]. No evidences of a protective effect were found in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most attention was paid to digestive system disorders: stomach and intestine cancer [93][94][95][96], colorectal adenoma [97], various other gastrointestinal disorders [98,99], and liver diseases [100]. However, the range of works included also other types of diseases: cardiovascular, nervous, osteoarticular, renal, endocrine, ocular, dermal, and nonorgan-specific [98,99].…”
Section: Meta-analysis Of Results Of Studies On the Effectiveness Of mentioning
confidence: 99%
“…Водорозчинні вітаміни, зокрема, групи В вважають допоміжними компонентами ком-плексного лікування для покращання якості життя хворих і кращої переносності хіміо-та радіотерапії [1][2][3][4][5][6][7][8][9][10]. Äуже важливими є докази безпеки лікування з застосуванням комплексів вітамінів, включаючи вітаміни групи В, і їх позитивного впливу на загаль-ний стан хворих, відсутність при цьому активації метастазування [11][12][13][14].…”
Section: дåяê³ çàêîíîì³ðíîñò³ çàбåçïåчåííя в³òàì³íàìè ãðóïè в хвîðèх unclassified